Interfaith Marriage of North Sulawesi Multicultural Community in Minority Fiqh Perspective - Edi Gunawan; Budi Rahmat Hakim; Reza Adeputra Tohis; Imam Mash’ud (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2024)
The teachings of Islam and the Indonesian constitution clearly prohibit interfaith marriage. However, some Muslim communities in North Sulawesi as a minority group have entered into interfaith marriages. Therefore, this study aims to analyze the phenomenon of interreligious marriage in North Sulawesi and the achievement of minority fiqh objectives in interfaith families. This research is a field research that uses qualitative methods with a phenomenological approach. Data collection was conducted through interviews with informants consisting of 5 interfaith marriage actors, 1 village official, and 1 religious leader. The results showed that the main motivation for interfaith couples to marry is mutual love. They also tend to get support from their respective extended families so that the marriage runs relatively smoothly and safely. The objectives of minority fiqh are achieved in interfaith marriages in the multicultural society of North Sulawesi. Minority fiqh can be an approach in interfaith marriages in multicultural societies where Muslims are a minority, without losing their Islamic essence, it is based on the fiqh rule that changes in law can occur due to changes in times and places. Minority jurisprudence can be an alternative basis for the sustainability of interfaith families in North Sulawesi that are able to maintain their Islamic identity while still respecting their partner's beliefs.